A New Technology of Remote Sensing Image Fusion - Wei Feng; Wenxing Bao (Institute of Advanced Engineering and Science, 2012)
To resolve the problem of multi-spectral remote sensing image fusion ?in this paper, we put forward an algorithm based on the wavelet packet and pulse-coupled neural network (PCNN) of remote sensing image fusion .The algorithm will be carried out as follows. Firstly, the TM images will be converted into HIS space, and then the luminance component and the high-resolution image will be broken into multi-scale by wavelet packet. Secondly, according to the frequency domain characteristics of the wavelet packet decomposition, we respectively use a method of weighted average in the low-frequency domain and a method of PCNN in the high frequency domain to select reconstruction coefficient.We can get a fused luminance component by taking inverse wavelet packet transform to be reconstructed. Finally, we can obtain the fusion image by taking inverse HIS transform. The experimental results show that the algorithm can be better to retain the image edge and texture details.Keywords: image fusion; HSI; wavelet packet; pulse coupled neural networks DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.617